Best practices of online education : a guide for Christian higher education - Maddix, Mark A., 1965-; Estep, James Riley, 1963-; Lowe, Mary Ella (Emerald Publishing Limited : Information Age Publishing Inc., 2012)
The book provides best practices from online educators who are engaged in online teaching and program development in Christian higher education. It also explores the distinct aspects of teaching and developing online courses and programs from a Christian perspective and within Christian higher education institutions. As such it is can serve as a ready resource for academic administrators and professors, novices and veterans at online program development and instruction.
Keywords: Christian universities and colleges -- United States -- Data processing.; Computer-assisted instruction -- United States.; Computers -- Educational Software.; Educational equipment and technology, computer-aided learning (CAL); Information technology: general topics.; elektronické knihy; electronic books